Talon cusp of mandibular anterior tooth: A rare case - A.N. Sulabha; Nikhat M. Attar (Al Ameen Medical College, 2018)
The talon cusp, or dens evaginatus of mandibular anterior teeth, is a very rare dental developmental anomaly which is characterized by the presence of an accessory cusp like structure projecting from the cingulum area or cementoenamel junction. This dental anomaly was first described by Mitchell" as a "process of hornlike shape, curving from the base downward to the cutting edge". Later it was named as talons cusp by Mellor and Ripa because of its resemblance to that of the shape of an eagle's talon [1].